Static aerobic composting of municipal sewage sludge with forced ventilation: Using matured compost as bulking conditioner - Ouyang, Jian-xin; Shi, Zhou; Zhong, Hua; Liu, Wei; Chai, Qi; Yuan, Xing-zhong (Journal of Central South University, 2014)
Static aerobic composting of municipal sewage sludge with forced ventilation or air ventilation using matured compost as bulking conditioner was investigated. Physical and chemical parameters, e.g., temperature, moisture content, VSS, CODcr, pH, and germination index (GI), were analyzed to characterize the composting process. Fermentation starts quickly in both forced and air ventilation compost heaps and reaches high-temperature stage after 2 d, owing to the bulking function of matured compost. Compared to air ventilation, however, forced ventilation enables the high-temperature stage to last longer for approximately 7 d. The moisture content of both compost bodies decreases from 62% to about 50% as a result of evaporation, and it decreases slightly faster in forced ventilation compost heap after 13 d due to the higher temperature and better ventilation condition. Although no obvious differences of VSS and pH are observed between both compost heaps, the soluble COD Cr and GI show differences during the second half period of fermentation. In forced ventilation compost, the soluble COD Cr has a small rebound after 13 d, and GI decreases from 46% to 35% but then increases. These results show that in general, the matured compost is a good conditioner and force ventilation with a proper air supply strategy can be more efficient than air ventilation.